The Sharing Economy: Personal Norm and Awareness to Participate in Collaborative Consumption - Cheng, Chuah Soo; Azhar, Nur Azirah Zahida Mohamad (Advances in Social Sciences Research Journal, 2023)
The emergence of sharing economy give rise to the popularity of collaborative consumption, which is known as events in which people consume items or services in joint activities with others. It being said that personal norms act as a major component in examining consumer intentions. The personal norms are based on individual values and motivation to protect them with appropriate behaviour. On the other hand, awareness of collaborative consumption found to have an impact on personal norm, thus influence the collaborative consumption. This study conducted a self-administrated survey to collect data from respondents in Klang Valley through purposive and convenience sampling methods. A total of 825 respondents were collected through the internet. Analysis method of Structural equation modelling-partial least squares estimation was applied to analyse the data in the study using SmartPLS version 3.3.9 software. The analysis of SEM-PLS comprises the measurement model on convergent validity analysis including factor loadings, average variance extracted (AVE), and composite reliability (CR). The findings revealed that awareness and responsibility of collaborative consumption have significant effect on personal norm. This indicates that consumers’ cognitive appraisal of potential consequences and accountability has significant influence on their pro-environmental behaviour. Furthermore, the findings showed a positive significant of personal norm and awareness of CC on collaborative consumption participation, indicating that collaborative consumption participation intention is due to a perceived obligation towards the societal and ecological surroundings.